Crack-free nickel-based cast superalloy as well as preparation method and application thereof

Through laser powder bed melting forming technology, the synergistic effect of continuous laser and pulsed laser is used to achieve crack suppression of high-γ' phase nickel-based cast high-temperature alloys, and a crack-free γ' phase reinforced nickel-based cast high-temperature alloy with high strength and excellent plasticity is prepared, solving the problems of poor welding properties and cracks in traditional alloys, and is suitable for complex components of gas turbines and aircraft engines.

CN119876670APending Publication Date: 2025-04-25CHINA UNITED GAS TURBINE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510053177.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The high-γ' phase nickel-based cast high-temperature alloy contains high content of Al, Ti, Hf and other elements, and has poor weldability and a large number of cracks, which affects the service performance of the gas turbine blades.

Method used

Using laser powder bed melting forming technology, through the dual laser synergistic coupling of continuous laser and pulsed laser, grain refinement and thermal stress are achieved and crack formation is suppressed. Specific steps include preliminary scanning to achieve forming and preheating, following the scanning to regulate the forming temperature field and microstructure, and thermal isostatic pressure to bridge the defect.

Benefits of technology

The preparation of crack-free γ' phase-reinforced nickel-based cast high-temperature alloy has been achieved, with high strength, excellent plasticity and good isotropy, and is suitable for blades and hot end components of gas turbines or aircraft engines.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876670A_ABST
    Figure CN119876670A_ABST
Patent Text Reader

Abstract

The invention discloses a crack-free nickel-based cast superalloy and a preparation method and application thereof.The preparation method of the crack-free nickel-based cast superalloy comprises the following steps that (1) nickel-based cast superalloy powder is laid, preliminary scanning is conducted through continuous laser, and preliminary forming and preheating are achieved; (2) in an area scanned by the continuous laser, pulse laser is adopted for follow-up scanning, and a formed part is obtained; and (3) carrying out hot isostatic pressing treatment on the formed part to obtain the crack-free nickel-based cast superalloy. According to the crack-free high-gamma-'phase nickel-based cast superalloy, the laser powder bed melting forming technology is adopted, and crack inhibition of the high-gamma-'phase nickel-based cast superalloy is achieved through the continuous laser and pulse laser synergistic coupling effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of preparation of metal materials, and in particular to a crack-free nickel-based cast high-temperature alloy and a preparation method and application thereof. Background Art

[0002] The independent research and development of gas turbines is a national strategic industry. The traditional forging, casting, welding and other methods are used to prepare large and complex structural parts, which have long processes, complex processes, high requirements for manufacturing equipment, and difficult forming technology. Laser powder bed melting forming technology can meet the requirements of gas turbines for "shape control" of complex components. However, since high γ' phase nickel-based casting high-temperature alloy is a typical casting high-temperature alloy, it contains high contents of Al, Ti, Hf and other elements, has poor weldability and a large number of cracks. Removing elements such as Al, Ti, and Hf can increase the weldability of the alloy, but it will reduce the high-temperature strength, fatigue and creep properties of the material, affecting the service performance of gas turbine blades. Therefore, it is urgent to develop a method for preparing crack-free high γ' phase nickel-based casting high-temperature alloy. Summary of the invention

[0003] The present invention is based on the inventor's discovery and understanding of the following facts and problems: High γ' phase nickel-based casting high temperature alloy is a typical casting high temperature alloy, containing high content of Al, Ti, Hf and other elements, poor weldability, and a large number of cracks. When high γ' phase nickel-based casting high temperature alloy is formed by laser powder bed melting, high thermal stress and coarse columnar crystal structure with high content of large-angle grain boundaries are the root causes of cracks.

[0004] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the embodiments of the present invention provide a crack-free nickel-based cast high-temperature alloy and a preparation method and application thereof, wherein the crack-free high γ' phase nickel-based cast high-temperature alloy adopts laser powder bed melting forming technology, and the continuous laser and pulse laser dual laser synergistic coupling effect is used to achieve grain refinement and reduce thermal stress, and to achieve crack suppression of the high γ' phase nickel-based cast high-temperature alloy, thereby obtaining a crack-free γ' phase strengthened nickel-based cast high-temperature alloy.

[0005] The embodiment of the present invention provides a method for preparing a crack-free nickel-based cast high-temperature alloy, comprising the following steps:

[0006] (1) Laying nickel-based casting high-temperature alloy powder, using continuous laser for preliminary scanning to achieve preliminary forming and preheating;

[0007] (2) In the area scanned by the continuous laser, a pulsed laser is used for follow-up scanning to obtain a formed part;

[0008] (3) The formed part is subjected to hot isostatic pressing to obtain a crack-free nickel-based cast high-temperature alloy.

[0009] The advantages and technical effects brought by the preparation method of the crack-free nickel-based cast high-temperature alloy of the embodiment of the present invention are as follows: the crack-free high-γ' phase nickel-based cast high-temperature alloy adopts laser powder bed melting forming technology, and the synergistic coupling of continuous laser and pulsed laser dual lasers, by regulating the forming temperature field and material microstructure, to achieve grain refinement and reduce thermal stress, thereby achieving crack suppression of the high-γ' phase nickel-based cast high-temperature alloy, and obtaining a crack-free γ' phase strengthened nickel-based cast high-temperature alloy.

[0010] In the embodiment of the present invention, a continuous laser is first used to perform a preliminary scan on the powder, so that the powder surface is melted while the core powder is not melted, so as to achieve the purpose of preliminary bonding of the powder, realize the preheating and preliminary forming of the powder, reduce the thermal stress during the subsequent pulse laser follow-up scanning forming, and reduce the influence of the external factor of crack formation, namely the thermal stress, on the forming quality. In addition, the preliminary forming layer after the preliminary scanning of the continuous laser can reduce the influence of powder splashing during the pulse laser follow-up scanning forming process on the forming quality. In the forming area scanned by the continuous laser, the initial forming layer is followed by scanning and forming by the pulse laser. On the basis of reducing the thermal stress, compared with the continuous laser of the continuous stable melting solidification forming, the pulse laser has the forming characteristics of non-interference between the molten pools, and the molten pool size is smaller. Under the same substrate temperature conditions, the temperature gradient is larger, the cooling speed is faster, and grain refinement can be achieved. The synergistic coupling of the continuous laser and the pulse laser can achieve crack suppression under the joint action of reducing thermal stress and grain refinement. The pulse laser followed by the continuous laser scanning strategy is adopted. The powder is first preliminarily scanned by the continuous laser, and the pulse laser is used to follow the forming area scanned by the continuous laser to control the forming temperature field and microstructure, thereby achieving crack suppression. After the pulse laser follow-up scanning, hot isostatic pressing treatment is performed to further bridge the tiny defects of the printed structure and obtain a denser, crack-free nickel-based casting high-temperature alloy.

[0011] In some embodiments, in step (1), the nickel-based casting high-temperature alloy powder includes: Al: 1.0-8.0wt.%; Ti: 0.5-3.0wt.%; Ta: 1.0-4.5wt.%; Hf: 0.3-2.5wt.%; W: 5.0-10.5wt.%; Co: 5.0-11.0wt.%; Cr: 4.0-10.3%; and the rest is Ni.

[0012] In some embodiments, the nickel-based casting high-temperature alloy powder further includes: Mo: ≤1.5wt.%; Zr: ≤1.0wt.%; B: ≤1.0wt.%; C: ≤0.3wt.%.

[0013] In some embodiments, in step (1), the laser power of the continuous laser is 50 to 200 W;

[0014] And / or, the scanning speed of the continuous laser is 100 to 1500 mm / s;

[0015] And / or, the scanning interval of the continuous laser is 50-120 μm;

[0016] And / or, the continuous laser preliminary scanning is performed under an inert atmosphere.

[0017] In some embodiments, in step (2), the area where the pulse laser follows the scanning is an area where the laser is continuously scanned and the temperature is not less than 500°C.

[0018] In some embodiments, in step (2), the laser power of the pulsed laser is 150-300W;

[0019] And / or, the frequency of the pulsed laser is 500-10000 Hz;

[0020] And / or, the scanning speed of the pulse laser is 100 to 1000 mm / s;

[0021] And / or, the pulse width of the pulse laser is 10 -8 ~10 -3 s;

[0022] And / or, the pulse laser follow-up scanning is performed under an inert atmosphere.

[0023] In some embodiments, in step (3), the pressure of the hot isostatic pressing treatment is not less than 150 MPa;

[0024] And / or, the holding temperature of the hot isostatic pressing treatment is 1150-1260°C;

[0025] And / or, the holding time of the hot isostatic pressing treatment is 2 to 6 hours;

[0026] And / or, the heating rate of the hot isostatic pressing treatment is not higher than 10°C / min;

[0027] And / or, the cooling rate of the hot isostatic pressing treatment is not higher than 10°C / min.

[0028] The embodiment of the present invention provides a crack-free nickel-based cast high-temperature alloy, which is prepared by the preparation method described in the embodiment of the present invention. In the embodiment of the present invention, the crack-free high-γ' phase nickel-based cast high-temperature alloy has high strength and excellent plasticity, and exhibits good isotropy.

[0029] In some embodiments, the crack-free nickel-based cast high-temperature alloy has a tensile strength greater than 1200 MPa, a yield strength greater than 800 MPa, and an elongation greater than 13%.

[0030] In some embodiments, the crack-free nickel-based cast high-temperature alloy is a γ' phase strengthened nickel-based cast high-temperature alloy.

[0031] The embodiment of the present invention provides an application of a crack-free nickel-based cast high-temperature alloy, a gas turbine or an aircraft engine. In the embodiment of the present invention, the crack-free high-γ' phase nickel-based cast high-temperature alloy has high strength and excellent plasticity, and exhibits good isotropy, and is suitable for gas turbines or aircraft engines, especially gas turbine blades, and can meet the requirements of gas turbines for "shape control" of complex components, which is conducive to improving the service performance of gas turbines. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a metallographic photograph of the Mar M247 high temperature alloy in Comparative Example 4.

[0033] Figure 2 This is a metallographic photograph of the Mar M247 high-temperature alloy in Example 1.

[0034] Figure 3 The difference in heating and cooling effects of different pulse laser parameters on the sample in Example 2.

[0035] Figure 4 This is a metallographic photograph of the Mar M247 high temperature alloy in Comparative Example 1.

[0036] Figure 5 This is a metallographic photograph of the Mar M247 high temperature alloy in Comparative Example 2.

[0037] Figure 6 This is a metallographic photograph of the Mar M247 high temperature alloy in Comparative Example 3. DETAILED DESCRIPTION

[0038] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0039] A method for preparing a crack-free nickel-based cast high-temperature alloy according to an embodiment of the present invention comprises the following steps:

[0040] (1) Laying nickel-based casting high-temperature alloy powder, using continuous laser for preliminary scanning to achieve preliminary forming and preheating;

[0041] (2) In the area scanned by the continuous laser, a pulsed laser is used for follow-up scanning to obtain a formed part;

[0042] (3) The formed part is subjected to hot isostatic pressing to obtain a crack-free nickel-based cast high-temperature alloy.

[0043] The preparation method of the crack-free nickel-based cast high-temperature alloy in the embodiment of the present invention adopts laser powder bed melting forming technology, and the synergistic coupling of continuous laser and pulsed laser dual lasers. By regulating the forming temperature field and material microstructure, grain refinement and thermal stress reduction are achieved, thereby achieving crack suppression of the high-γ'-phase nickel-based cast high-temperature alloy, and obtaining a crack-free γ'-phase strengthened nickel-based cast high-temperature alloy.

[0044] In the embodiment of the present invention, a continuous laser is first used to perform a preliminary scan on the powder, so that the powder surface is melted while the core powder is not melted, so as to achieve the purpose of preliminary bonding of the powder, realize the preheating and preliminary forming of the powder, reduce the thermal stress during the subsequent pulse laser follow-up scanning forming, and reduce the influence of the external factor of crack formation, namely the thermal stress, on the forming quality. In addition, the preliminary forming layer after the preliminary scanning of the continuous laser can reduce the influence of powder splashing during the pulse laser follow-up scanning forming process on the forming quality. In the forming area scanned by the continuous laser, the initial forming layer is followed by scanning and forming by the pulse laser. On the basis of reducing the thermal stress, compared with the continuous laser of the continuous stable melting solidification forming, the pulse laser has the forming characteristics of non-interference between the molten pools, and the molten pool size is smaller. Under the same substrate temperature conditions, the temperature gradient is larger, the cooling speed is faster, and grain refinement can be achieved. The synergistic coupling of the continuous laser and the pulse laser can achieve crack suppression under the joint action of reducing thermal stress and grain refinement. The pulse laser followed by the continuous laser scanning strategy is adopted. The powder is first preliminarily scanned by the continuous laser, and the pulse laser is used to follow the forming area scanned by the continuous laser to control the forming temperature field and microstructure, thereby achieving crack suppression. After the pulse laser follow-up scanning, hot isostatic pressing treatment is performed to further bridge the tiny defects of the printed structure and obtain a denser, crack-free nickel-based casting high-temperature alloy.

[0045] In some embodiments, the method for preparing the crack-free nickel-based cast high-temperature alloy uses a 3D printing device;

[0046] Optionally, the 3D printing equipment may be SLM Solutions 280HL and / or Renishaw AM 250;

[0047] Optionally, a crack-free nickel-based cast high-temperature alloy is prepared by slicing using a 3D printing device;

[0048] Optionally, the required shape is designed by CAD software, sliced, and imported into a 3D printing device, and the method for preparing the crack-free nickel-based cast high-temperature alloy is performed by the 3D printing device to prepare the crack-free nickel-based cast high-temperature alloy;

[0049] Optionally, nickel-based casting high-temperature alloy powder is laid on the substrate; the layer thickness of the powder is 25-50 μm, specifically, for example, 25 μm, 30 μm, 40 μm, 50 μm;

[0050] Optionally, the shaped piece is cut from the substrate;

[0051] Optionally, the method for preparing the crack-free nickel-based cast high-temperature alloy comprises the following steps:

[0052] 1) Design the required shape through CAD software, slice it, and import it into 3D printing equipment;

[0053] 2) Laying nickel-based casting high-temperature alloy powder, using continuous laser for preliminary scanning to achieve preliminary forming and preheating;

[0054] 3) In the area scanned by the continuous laser, a pulsed laser is used for follow-up scanning to obtain a formed part;

[0055] 4) The formed part is subjected to hot isostatic pressing to obtain a crack-free nickel-based cast high-temperature alloy.

[0056] In some embodiments, nickel-based casting high-temperature alloy powder is laid, and the layer thickness of the powder is 25-50 μm, specifically, for example, 25 μm, 30 μm, 40 μm, 50 μm.

[0057] In some embodiments, the scanning strategy is a stripe mode, and the inter-layer rotation between different layers is accompanied by laser scanning, and the rotation angle is 45°-67°-135°.

[0058] In some embodiments, in step (1), the nickel-based casting high-temperature alloy powder includes: Al: 1.0-8.0wt.%; Ti: 0.5-3.0wt.%; Ta: 1.0-4.5wt.%; Hf: 0.3-2.5wt.%; W: 5.0-10.5wt.%; Co: 5.0-11.0wt.%; Cr: 4.0-10.3%; the rest is Ni;

[0059] In a specific embodiment, Al may be 1.0 wt.%, 2.0 wt.%, 3.0 wt.%, 4.0 wt.%, 5.0 wt.%, 6.0 wt.%, 7.0 wt.%, 8.0 wt.%;

[0060] Ti may be 0.5wt.%, 1.0wt.%, 1.5wt.%, 2.0wt.%, 2.5wt.%, 3.0wt.%;

[0061] Ta may be 1.0wt.%, 1.5wt.%, 2.0wt.%, 2.5wt.%, 3.0wt.%, 4.0wt.%, 4.5wt.%;

[0062] Hf may be 0.3wt.%, 0.5wt.%, 1.0wt.%, 1.5wt.%, 2.0wt.%, 2.5wt.%;

[0063] W may be 5.0wt.%, 6.0wt.%, 7.0wt.%, 8.0wt.%, 9.0wt.%, 10.0wt.%, 10.5wt.%;

[0064] Co may be 5.0wt.%, 6.0wt.%, 7.0wt.%, 8.0wt.%, 9.0wt.%, 10.0wt.%, 10.5wt.%, 11.0wt.%;

[0065] Cr may be 4.0 wt.%, 5.0 wt.%, 6.0 wt.%, 7.0 wt.%, 8.0 wt.%, 9.0 wt.%, 10.0 wt.%, 10.3%.

[0066] In the embodiment of the present invention, the γ' phase strengthened nickel-based cast high temperature alloy is a typical cast high temperature alloy, which contains a high content of elements such as Al, Ti, Hf, etc., has poor weldability, and has a large number of cracks. However, removing elements such as Al, Ti, Hf, etc. can increase the weldability of the alloy, but will reduce the high temperature strength, fatigue and creep properties of the material, affecting the service performance of the gas turbine blades. The present invention can prepare a crack-sensitive alloy to obtain a crack-free γ' phase strengthened nickel-based cast high temperature alloy.

[0067] In some embodiments, in step (1), the nickel-based casting high-temperature alloy powder further includes: Mo: ≤1.5wt.%; Zr: ≤1.0wt.%; B: ≤1.0wt.%; C: ≤0.3wt.%.

[0068] In some embodiments, in step (1), the particle size of the nickel-based cast high-temperature alloy powder is 10-60 μm, specifically, for example, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm; optionally, the nickel-based cast high-temperature alloy powder is spherical or quasi-spherical; and / or the fluidity of the nickel-based cast high-temperature alloy powder is lower than 20 s / 50 g. In the embodiment of the present invention, the particle size of the alloy powder is 10-60 μm, which is conducive to good spreading of the powder and control of the powder layer thickness, and is conducive to printing and forming.

[0069] In some embodiments, in step (1), there is no particular limitation on the method for preparing the nickel-based cast high-temperature alloy powder. For example, the nickel-based cast high-temperature alloy powder can be prepared by a vacuum atomization method.

[0070] In some embodiments, in step (1), the laser power of the continuous laser is 50 to 200 W, specifically, for example, 50 W, 100 W, 150 W, 175 W, 190 W, 195 W, 200 W; and / or the scanning speed of the continuous laser is 100 to 1500 mm / s, specifically, for example, 100 mm / s, 500 mm / s, 750 mm / s, 900 mm / s, 950 mm / s, 1000 mm / s, 1500 mm / s. In the embodiment of the present invention, a low-power, low-scanning-speed continuous laser is first used to preliminarily scan the powder. The laser power of the continuous laser is lower than the power of the usual continuous laser single laser alloy preparation, and the scanning speed is lower than the scanning rate of the usual continuous laser single laser alloy preparation, which can make the powder surface melt while the core powder does not melt, so as to achieve the purpose of preliminary bonding of the powder, realize the powder preheating and preliminary forming of the powder, reduce the thermal stress during the subsequent pulse laser follow-up scanning forming, reduce the external factor of crack formation, namely the influence of thermal stress on the forming quality, and inhibit crack initiation and expansion. When the laser power of the continuous laser is too high, printing and forming can be achieved in the continuous laser scanning stage, and original cracks will be formed in this step, which is not conducive to the subsequent forming of crack-free blocks; when the scanning speed is too high, the melting path is unstable, which is not conducive to stable preforming, and affects the final forming quality under the subsequent pulse laser action.

[0071] In some embodiments, in step (1), the spot diameter of the continuous laser is 30-150 μm, specifically, for example, 30 μm, 50 μm, 100 μm, 150 μm; and / or the scanning interval of the continuous laser is 50-120 μm, specifically, for example, 50 μm, 80 μm, 100 μm, 120 μm.

[0072] In some embodiments, in step (1), the continuous laser preliminary scanning is performed under an inert atmosphere. Optionally, the inert atmosphere includes at least one of argon, nitrogen, and carbon dioxide.

[0073] In some embodiments, in the step (2), a pulsed laser is used to perform follow-up scanning in the area scanned by the continuous laser to obtain a formed part; optionally, the following refers to the pulsed laser following the continuous laser to scan, and following in time and / or space.

[0074] In some embodiments, in step (2), the area followed by the pulse laser scanning is an area continuously scanned by the laser and the temperature is not less than 500°C, optionally, not less than 500°C, not less than 600°C, not less than 700°C, not less than 800°C; the laser power of the pulse laser is 150-300W, specifically, for example, 150W, 200W, 210W, 250W, 300W; and / or the frequency of the pulse laser is 500-10000HZ, specifically, for example, 500HZ, 1000HZ, 2000HZ, 5000HZ, 10000HZ; and / or the scanning speed of the pulse laser is 100-1000mm / s, specifically, for example, 100mm / s, 500mm / s, 900mm / s, 950mm / s, 1000mm / s. In the embodiment of the present invention, on the basis of continuous laser to reduce powder splash and thermal stress, pulse laser tracking scanning is used to reduce the size of the molten pool and the interaction between the molten pools, and finally crack suppression and material and component forming are achieved. When the temperature of the forming area scanned by the continuous laser has not yet dropped to 500°C, a pulse laser with high power, low frequency and low speed characteristics is used to follow the scanning and forming of the initial forming layer. On the basis of reducing thermal stress, compared with the continuous laser for continuous stable melting channel solidification forming, the pulse laser with low frequency and low speed characteristics has the forming characteristics of non-interference between the molten pools, and the molten pool size is small. Under the same substrate temperature conditions, the temperature gradient is larger, the cooling speed is faster, and grain refinement can be achieved. A pulse laser with high power, low frequency and low speed characteristics is used to follow the scanning of the forming area, and the forming temperature field and microstructure are regulated. Crack suppression can be achieved under the joint action of reducing thermal stress and grain refinement. If the laser power of the pulsed laser is too low, the powder cannot be completely melted and good forming cannot be achieved; when the frequency of the pulsed laser is too high, the independence of each molten pool cannot be guaranteed, which will affect the microstructure of the formed sample and is not conducive to tissue refinement; when the scanning speed of the pulsed laser is too high, it cannot ensure synchronization with the previous continuous laser, and the original design intention of laser follow-up scanning cannot be achieved.

[0075] In some embodiments, the pulse width of the pulse laser is 10 -8 ~10 -3 s; and / or, the waveform of the pulse laser is an arbitrary waveform, optionally, a rectangular wave; and / or, the spot diameter of the pulse laser is ≤150μm, specifically, for example, 30μm, 50μm, 100μm, 150μm; and / or, the pulse laser follow-up scanning is performed in an inert atmosphere, optionally, the inert atmosphere includes at least one of argon, nitrogen, and carbon dioxide.

[0076] In some embodiments, in step (3), the pressure of the hot isostatic pressing treatment is not less than 150 MPa, specifically, for example, 150 MPa, 200 MPa, 220 MPa, 250 MPa; and / or, the holding temperature of the hot isostatic pressing treatment is 1150-1260°C, specifically, for example, 1150°C, 1170°C, 1200°C, 1220°C, 1260°C; and / or, the holding time of the hot isostatic pressing treatment is 2-6 h, specifically, for example, 2 h, 3 h, 4 h, 5 h, 6 h; and / or, the heating rate of the hot isostatic pressing treatment is not higher than 10 ℃ / min, specifically, for example, 10℃ / min, 7℃ / min, 5℃ / min, 3℃ / min, 2.5℃ / min, 2℃ / min, 1℃ / min, optionally, less than 10℃ / min, optionally, less than 3℃ / min; and / or, the cooling rate of the hot isostatic pressing treatment is not higher than 10℃ / min, specifically, for example, 10℃ / min, 7℃ / min, 5℃ / min, 3℃ / min, 2.5℃ / min, 2℃ / min, 1℃ / min, optionally, less than 10℃ / min, optionally, less than 3℃ / min. In the embodiment of the present invention, the hot isostatic pressing treatment can bridge the tiny defects in the printed tissue. The pressure of the hot isostatic pressing treatment is greater than 150MPa, which is conducive to better bridging the defects. The holding temperature of the hot isostatic pressing treatment is 1150-1260℃, which can achieve defect bridging and ensure that it is below the melting point of the alloy. The heating and cooling rate of hot isostatic pressing treatment is not higher than 10°C / min. A smaller heating and cooling rate can keep the material in a balanced state as much as possible, reduce the thermal stress caused by excessive heating and cooling rate, and reduce the crack sensitivity of the sample.

[0077] A crack-free nickel-based cast high-temperature alloy according to an embodiment of the present invention is prepared by the preparation method described in the embodiment of the present invention. In the embodiment of the present invention, the crack-free high-γ' phase nickel-based cast high-temperature alloy has high strength and excellent plasticity, and exhibits good isotropy.

[0078] In some embodiments, the crack-free nickel-based cast high-temperature alloy has a tensile strength greater than 1200 MPa, a yield strength greater than 800 MPa, and an elongation greater than 13%.

[0079] In some embodiments, the crack-free nickel-based cast high-temperature alloy is a γ' phase strengthened nickel-based cast high-temperature alloy; optionally, the crack-free nickel-based cast high-temperature alloy includes crack-free Mar M247.

[0080] An application of a crack-free nickel-based cast high-temperature alloy in an embodiment of the present invention is used in a gas turbine or an aircraft engine. In the embodiment of the present invention, the crack-free high-γ' phase nickel-based cast high-temperature alloy has high strength and excellent plasticity, and exhibits good isotropy, and is suitable for gas turbines or aircraft engines, especially gas turbine blades, and can meet the requirements of gas turbines for "shape control" of complex components, which is conducive to improving the service performance of gas turbines.

[0081] In some embodiments, for use in gas turbine blades.

[0082] In some embodiments, it is used in a gas turbine hot end component.

[0083] In some embodiments, it is used in the hot end components of aircraft engines.

[0084] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0085] Example 1

[0086] A method for preparing a crack-free nickel-based cast high-temperature alloy comprises the following steps:

[0087] (1) Taking Mar M247 high-temperature alloy with the strongest crack sensitivity as the model material, vacuum atomization powder making technology was used to obtain nickel-based casting high-temperature alloy powder. The alloy powder composition is: Co: 10.52%, Cr: 8.26%, Mo: 0.60%, W: 9.80%, Ta: 3.00%, Ti: 1.11%, Al: 5.68%, Hf: 1.42%, Zr: 0.054%, B: 0.014%, C: 0.15%, and the remainder is Ni (in mass percentage).

[0088] The particle size of the alloy powder is 15-53 μm, D10 is about 19.64 μm, D50 is about 35.27 μm, D90 is about 56.85 μm, and the fluidity of the alloy powder is less than 14.57 s / 50 g;

[0089] (2) A low-power, low-scanning-speed continuous laser was used to perform preliminary scanning on the powder to achieve preliminary forming and preheating. The laser power was 50 W, the scanning speed was 100 mm / s, the layer thickness was 30 μm, the scanning spacing was 70 μm, and the scanning strategy was stripe mode. The laser scanning was accompanied by interlayer rotation between different layers, and the rotation angle was 45°-67°-135°.

[0090] (3) In the range where the temperature of the area continuously scanned by the laser is higher than 800°C, a pulsed laser with high power, low frequency and low speed characteristics is used for follow-up scanning to obtain a formed part; wherein the pulsed laser power is 300 W, the frequency is 500 Hz, the scanning speed is 100 mm / s, and the pulse width is 1*10 -3 s;

[0091] (4) The printed parts were subjected to hot isostatic pressing treatment. The pressure of the hot isostatic pressing treatment was 250 MPa, the holding time was 4 h, the holding temperature was 1200°C, and the heating and cooling rate was 2.5°C / min, thereby obtaining a crack-free nickel-based cast high-temperature alloy.

[0092] Table 1 Room temperature mechanical properties of crack-free Mar M247 nickel-based cast high temperature alloy in Example 1

[0093] Tensile strength / MPa Yield strength / MPa Elongation / % 1274 811 16.7

[0094] from Figure 2 It can be seen that the prepared Mar M247 nickel-based cast high-temperature alloy has no cracks. Among the room temperature mechanical properties of the crack-free Mar M247 nickel-based cast high-temperature alloy, the tensile strength is close to 1300MPa, the yield strength is 811MPa, and the elongation is 16.7%. The prepared Mar M247 high-temperature alloy shows excellent strength and plasticity.

[0095] Example 2

[0096] The preparation method is the same as that of Example 1, except that in step (3), different pulse laser parameters are used, such as Figure 3 As shown in b);

[0097] The same 300W, 500Hz pulse laser parameters are used for tracking, scanning and printing:

[0098] In Example 1, when the pulse width is 1×10 -3 s, the powder bed is heated 500 times per second during the scanning process, the equivalent power of a single pulse during heating is 600 W, the action time is 0.001 s, and the cooling time is 0.001 s;

[0099] In Example 2, when a laser with a pulse width of 10 ns is used for scanning and printing, the powder bed is heated 500 times per second during the scanning process, and the equivalent power of a single pulse during heating is 6×10 6 kW, the action time is 10ns, and the cooling time is close to 0.002s.

[0100] Table 2 Room temperature mechanical properties of crack-free Mar M247 nickel-based cast high temperature alloy in Example 2

[0101] sample Tensile strength / MPa Yield strength / MPa Elongation / % Pulse width is 10ns 1290 810 17.2

[0102] By taking advantage of the difference in the single pulse energy of the pulsed laser and the effect on the high-temperature alloy, thermal field regulation is achieved, which plays a good role in promoting the reduction of thermal stress and the optimization of microstructure in the printing area of ​​the high-temperature alloy, and preparing a crack-free γ' phase strengthened nickel-based cast high-temperature alloy, further improving the mechanical properties of the crack-free nickel-based cast high-temperature alloy.

[0103] Example 3

[0104] The preparation method is the same as that of Example 1, except that in the step (1), the alloy powder components, in mass percentage, include: Co: 10.50%, Cr: 8.29%, Mo: 0.62%, W: 9.81%, Ta: 3.03%, Ti: 3.0%, Al: 8.0%, Hf: 1.40%, Zr: 0.056%, B: 0.015%, C: 0.14%, and the balance is Ni.

[0105] Table 3 Room temperature mechanical properties of crack-free nickel-based cast high temperature alloy in Example 3

[0106] Tensile strength / MPa Yield strength / MPa Elongation / % 1230 910 13.6

[0107] Comparative Example 1

[0108] The preparation method is the same as that in Example 1, except that step (3) is omitted, that is, pulse laser treatment is not performed. In step (2), the continuous laser power used is 180 W, the scanning speed is 800 mm / s, the layer thickness is 30 μm, the scanning spacing is 70 μm, the scanning strategy is stripe mode, and the interlayer rotation between different layers is accompanied by laser scanning, and the rotation angle is 45°-67°-135°.

[0109] like Figure 4 As shown, the microstructure of the alloy sample prepared by conventional continuous laser single laser powder bed printing strategy in Comparative Example 1 shows obvious cracks.

[0110] Comparative Example 2

[0111] The preparation method is the same as that of Example 1, except that step (2) is omitted, that is, continuous laser treatment is not performed, and the pulse laser power used is 300 W, the frequency is 500 Hz, the scanning speed is 100 mm / s, and the pulse width is 1*10 -3 s, the scanning interval was 70 μm, the layer thickness was 30 μm, the scanning strategy was stripe mode, and the laser scanning was accompanied by interlayer rotation between different layers, with a rotation angle of 45°-67°-135°.

[0112] like Figure 5As shown, the microstructure of the alloy sample prepared by pulse laser only in Comparative Example 2 shows obvious cracks.

[0113] Comparative Example 3

[0114] The preparation method is the same as that of Example 1, except that in step (3), after the continuous laser scanning area is cooled to room temperature, a pulsed laser with high power, low frequency and low speed characteristics is used for follow-up scanning.

[0115] like Figure 6 As shown, in Comparative Example 3, the microstructure of the alloy sample prepared by continuous laser scanning, cooling to room temperature, and then pulsed laser scanning can be seen to have obvious cracks. This is because the continuous laser preheating effect is lost during cooling to room temperature and then pulsed laser scanning is performed. During pulsed laser scanning, large thermal stress is generated due to the large temperature gradient and high cooling rate, which causes the sample to crack.

[0116] Comparative Example 4

[0117] The preparation method is the same as that of Example 1, except that step (4) is omitted, that is, hot isostatic pressing is not performed.

[0118] like Figure 1 As shown, the microstructure morphology of the alloy sample prepared without hot isostatic pressing in Comparative Example 4 shows that there are almost no cracks, but its mechanical properties are far inferior to those of the sample after hot isostatic pressing in Example 1, and both the tensile strength and elongation are reduced. This is because the hot isostatic pressing treatment is performed after the pulse laser follow-up scanning, which can further bridge the tiny defects of the printed structure and obtain a denser crack-free nickel-based cast high-temperature alloy.

[0119] Table 4 Room temperature mechanical properties of alloy samples in comparative example 4

[0120] Tensile strength / MPa Yield strength / MPa Elongation / % 1180 830 4.5

[0121] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0122] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.

Claims

1. A method for preparing a crack-free nickel-based cast high-temperature alloy, characterized in that: The following steps are involved: (1) Laying nickel-based casting high-temperature alloy powder, using continuous laser for preliminary scanning to achieve preliminary forming and preheating; (2) In the area scanned by the continuous laser, a pulsed laser is used for follow-up scanning to obtain a formed part; (3) The formed part is subjected to hot isostatic pressing to obtain a crack-free nickel-based cast high-temperature alloy.

2. The method for preparing a crack-free nickel-based cast high-temperature alloy according to claim 1, characterized in that: In the step (1), the nickel-based casting high-temperature alloy powder includes: Al: 1.0-8.0wt.%; Ti: 0.5-3.0wt.%; Ta: 1.0-4.5wt.%; Hf: 0.3-2.5wt.%; W: 5.0-10.5wt.%; Co: 5.0-11.0wt.%; Cr: 4.0-10.3%; and the rest is Ni.

3. The method for preparing a crack-free nickel-based cast high-temperature alloy according to claim 2, characterized in that: The nickel-based casting high-temperature alloy powder further includes: Mo: ≤1.5wt.%; Zr: ≤1.0wt.%; B: ≤1.0wt.%; C: ≤0.3wt.%.

4. The method for preparing a crack-free nickel-based cast high-temperature alloy according to claim 1, characterized in that: In the step (1), the laser power of the continuous laser is 50 to 200 W; And / or, the scanning speed of the continuous laser is 100 to 1500 mm / s; And / or, the scanning interval of the continuous laser is 50-120 μm; And / or, the continuous laser preliminary scanning is performed under an inert atmosphere.

5. The method for preparing a crack-free nickel-based cast high-temperature alloy according to claim 1, characterized in that: In the step (2), the area followed by the pulse laser scanning is an area continuously scanned by the laser and the temperature is not less than 500°C.

6. The method for preparing a crack-free nickel-based cast high-temperature alloy according to claim 1, characterized in that: In the step (2), the laser power of the pulsed laser is 150-300W; And / or, the frequency of the pulsed laser is 500-10000 Hz; And / or, the scanning speed of the pulse laser is 100 to 1000 mm / s; And / or, the pulse width of the pulse laser is 10 -8 ~10 -3 s; And / or, the pulse laser follow-up scanning is performed under an inert atmosphere.

7. The method for preparing a crack-free nickel-based cast high-temperature alloy according to claim 1, characterized in that: In the step (3), the pressure of the hot isostatic pressing treatment is not less than 150 MPa; And / or, the holding temperature of the hot isostatic pressing treatment is 1150-1260°C; And / or, the holding time of the hot isostatic pressing treatment is 2 to 6 hours; And / or, the heating rate of the hot isostatic pressing treatment is not higher than 10°C / min; And / or, the cooling rate of the hot isostatic pressing treatment is not higher than 10°C / min.

8. A crack-free nickel-based cast high-temperature alloy, characterized in that: The method is prepared according to any one of claims 1 to 7.

9. The crack-free nickel-based cast high-temperature alloy according to claim 8, characterized in that: The crack-free nickel-based cast high-temperature alloy has a tensile strength greater than 1200 MPa, a yield strength greater than 800 MPa, and an elongation greater than 13%; And / or, the crack-free nickel-based cast high-temperature alloy is a γ' phase strengthened nickel-based cast high-temperature alloy.

10. An application of the crack-free nickel-based cast high-temperature alloy as claimed in claim 8 or 9, characterized in that: For use in gas turbines or aircraft engines.